Slc39a2-Mediated Zinc Homeostasis Modulates Innate Immune Signaling in Phenylephrine-Induced Cardiomyocyte Hypertrophy - Fang, Yu; Wang, Shun; Lv, Jian; Zhao, Zhenyi; Guo, Ningning; Wu, Gang; Tong, Jingjing; Wang, Zhihua (Frontiers in Cardiovascular Medicine, 2021)
Zinc dyshomeostasis has been involved in the pathogenesis of cardiac hypertrophy; however, the dynamic regulation of intracellular zinc and its downstream signaling in cardiac hypertrophy remain largely unknown. Using Zincpyr1 staining, we found a significant decrease of intracellular Zinc concentration in phenylephrine (PE)-induced hypertrophy of neonatal rat ventricular myocytes (NRVMs). We then screened SLC39 family members responsible for zinc uptake and identified Slc39a2 as the only one altered by PE treatment. Slc39a2 knockdown in NRVMs reduced the intracellular Zinc level, and exacerbated the hypertrophic responses to PE treatment. In contrast, adenovirus-mediated Slc39a2 overexpression enhanced zinc uptake and suppressed PE-induced Nppb expression. RNA sequencing analysis showed a pro-hypertrophic transcriptome reprogramming after Slc39a2 knockdown. Interestingly, the innate immune signaling pathways, including NOD signaling, TOLL-like receptor, NFκB, and IRFs, were remarkably enriched in the Slc39a2-regulated genes. Slc39a2 deficiency enhanced the phosphorylation of P65 NFκB and STAT3, and reduced the expression of IκBα. Finally, the expression of IRF7 was significantly increased by Slc39a2 knockdown, which was in turn suppressed by IRF7 knockdown. Our data demonstrate that zinc homeostasis mediated by a Slc39a2/IRF7 regulatory circuit contributes to the alteration of innate immune signaling in cardiomyocyte hypertrophy.